HPTLC ASSAY FOR QUERCETIN AND RUTIN FLAVONOIDS IN ELEPHANTOPUS SCABER [LINN.] GROWN UNDER INDUCED HEAT STRESS CONDITION - VIJAY D. MENDHULKAR; SOPAN N. KHARAT (International Journal of Pharma and Bio Sciences, 2015)
The High Performance Thin Layer Chromatography (HPTLC) was carried out for the estimation of flavonoid content in the medicinal plant Elephantopus scaber [Linn], grown under heat stress conditions. The experimental plant system was subjected to the Heat Stress Induced (HSI) condition for two hours at 40 °C temperature daily for 7 days. Plants grown in Green House condition was taken as a control (GHC). The plant extracts were prepared in ethanol, methanol and water solvent system using sonication and maceration as variable extraction methods, independently. The mobile phase used was ethyl acetate: acetic acid: formic acid: water [100:11:11:27 v/v/v/v]. Detection and quantification was performed densitometrically at the wavelength of 254 nm and 366 nm for standard and all the plant samples, respectively. Our analysis in studying experimental system indicated remarkable fluctuations in the content of quercetin which ranges from 42.88 μg/ml (for GHC) to 143.74 μg/ml (for HSI). For the rutin, range was varying from 25.98 μg/ml (for GHC) to 49.43 μg/ml of plant material (for HSI). These findings provided the insight to understand the quantitative interference in secondary metabolites caused by stress conditions. In the present investigation the fluctuations in the flavonoid contents of the plant grown under stress condition were analyzed and the results obtained are discussed.